Mental disorder and social deviance. (4th July 2021) - Aftab, Awais; Rashed, Mohammed Abouelleil
Abstract: Social deviance refers to actions or behaviours that violate social norms. Since the declassification of homosexuality and development of DSM-III, one of the aims of a definition of mental disorder has been to make explicit the distinction between mental disorder and social deviance. It is well-recognized that psychiatric disorders frequently manifest as violations of social norms, and the validity of the distinction between disorder and deviance has been of great interest to philosophers of psychiatry. This article provides an overview of some of the major conceptual strategies that have been discussed as a means of discriminating between mental disorder and social deviance, and the extent to which these strategies can be said to be philosophically successful. Specifically, we review DSM's definition of mental disorder, notions of dysfunctions (commonsensical, clinical, naturalist), intrinsic and socially constituted distress, disability, 3E perspectives and functional norms, and ethical and political approaches to this question. Current philosophical strategies don't offer a distinct dividing line between disorder and deviance, but they help illuminate the relevant considerations involved. It may be concluded that the distinction between disorder and deviance is not simply discovered but also negotiated between competing values.